ECONOMICAL EFFICACY OF DIURON AS A WEED CONTROL OPTION IN RAINFED COTTON - M. MADHAVI, N.VARSHA and (The Journal of Research, PJTSAU, 2020)
Cotton, popularly known as â€œKing of fibreâ€ andÂ â€œWhite goldâ€ is the most important fibre and commercialÂ crop of India. The contribution of India to global cottonÂ fibre and edible oil production is 44 and 10%,Â respectively. Though India has the largest area (26%)Â of cotton in the world, due to its lower productivity theÂ share to the total world cotton production is only 12%.Â Weeds consume 5 to 6 times of N, 5 to 12 times of PÂ and 2 to 5 times of K more than cotton crop and thusÂ reduced the cotton yield from 54 to 85% (Jain et al.Â 1981). Cotton is very sensitive to crop-weed competitionÂ due to slow growth during early stage and widerÂ spacing. Weed infestation in cotton has been reportedÂ to offer severe competition causing yield reduction toÂ an extent of 74 percent (Shelke and Bhosle, 1990), 50Â to 85 percent (Sharma, 2008) depending upon theÂ nature and intensity of weeds. The critical period ofÂ weed competition in cotton was found to be 15 to 60Â days (Sharma, 2008). Weed management options should prevent weed interference, be economical andÂ sustainable, reduce weed seed bank in soil, preventÂ weed resistance and neither cause phytotoxicity toÂ cotton nor reduce the cotton lint quality. Manual weeding has traditionally been a labour intensive operation andÂ hence there is no other alternative rather than use ofÂ post emergence herbicides for control of weeds inÂ cotton. Herbicide is an economic alternative whenÂ labour is a problem or in abnormal weather situationÂ where fields are not accessible for mechanical weeding.